HUBUNGAN ANTARA SELF-ESTEEM DENGAN TINGKAT DEPRESI PADA IBU YANG MEMILIKI ANAK DOWN SYNDROME - Debri Pristinella; Raisa Vienlentia (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2018)
This research aimed to examine the relationship between self-esteem with level of depression among mother who have a children with down syndrome. Research hypothesis is there is a negative corelation between self-esteem and level of depression.the subjects of the research were 40 mothers who have a child with down syndrome. The sampling technique in this research uses purposive sampling. The data collected using two questionaires which were a self-esteem scale and level of depression scale adapted from Beck Depression Inventory scale. Result of item selection was 57 valid items with alpha cronbach reliability 0.919. Meanwhile depression level questionnaire (BDI) got 20 valid item with alpha cronbach reliability 0.821. Result of Spearman correlation technique were correlation coefficient -0.366 with the value of p=0,020 means that the value of p was lower than 0,05 (p